Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
When we subtract the second equation x-2y=9 from the first equation 4x-2y=-2, we get the value of x = 11/5.
Therefore, the required result is:
x = 11/5
Step-by-step explanation:
Given
The first equation
[tex]-4x-2y=-2[/tex]
The second equation
[tex]x-2y=9[/tex]
Let us subtract the second equation from the first equation
[tex]-4x-2y=-2[/tex]
[tex]-[/tex]
[tex]\:\underline{x-2y=9}[/tex]
[tex]-4x - 2y - (x - 2y) = -2 - 9[/tex]
[tex]-4x -2y -x + 2y = -2-9[/tex]
[tex]-5x = -11[/tex]
divide both sides by -5
[tex]\frac{-5x}{-5}=\frac{-11}{-5}[/tex]
Simplify
[tex]x=\frac{11}{5}[/tex]
Thus, when we subtract the second equation x-2y=9 from the first equation 4x-2y=-2, we get the value of x = 11/5.
Therefore, the required result is:
x = 11/5
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.